PENGARUH KUALITAS SISTEM DAN KUALITAS PELAYANAN APLIKASI E-ABSENSI SIAP TERHADAP KEPUASAN PEGAWAI DPPKB KARAWANG - Devita Novalia; Wanta Wanta; Flora Patricia Anggela (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze and examine the influence of system quality and service quality of the e-Absensi SIAP application on employee satisfaction at the Department of Population Control and Family Planning (DPPKB) Karawang Regency. Result: The results of the study through multiple linear regression analysis show that system quality has a positive and significant effect on employee satisfaction (sig 0.000), while service quality does not have a partially significant effect (sig 0.751). However, simultaneously both variables have a significant effect on employee satisfaction with a coefficient of determination of 28.5%. Conclution: The conclusion of this study is that the level of satisfaction of DPPKB Karawang employees in using e-Absensi SIAP is more determined by the reliability and ease of the system's technical features compared to the supporting service aspects. Contribution: This research contributes as a reference for local government agencies in conducting information technology evaluations to optimize human resource performance and satisfaction through strengthening digital infrastructure.